Development of Chinese Junior High School Students’ Creative Potential: Within-Person and Between-Person Effects of Student–Student Support and Need for Cognition - Chen, Peipei; Zhang, Jinghuan (Frontiers in Psychology, 2020)
A longitudinal study was conducted to examine the developmental trend of creative potential in Chinese junior high school students and the within-person and between-person effects of student-student support and need for cognition. Two hundred and fourteen Chinese junior high school students participated in the present study (Mean age = 13.29 years, SD = 0.49 years, 116 boys). Student-student support, need for cognition and creative potential were measured once per year for 3 years. Longitudinal multilevel models indicated that (1) Chinese junior high school students’ creative potential showed a downward trend from grade 7 to grade 9 (2) at the within-person level, time-varying student-student support positively predicted time-varying creative potential (3) at the within-person level, time-varying need for cognition moderated the positive link between time-varying student-student support and time-varying creative potential (4) at the between-person level, no support was found for the links between student-student support, need for cognition and creative potential. Specifically, average levels of student-student support neither significantly predicted initial levels and developmental rates of creative potential nor moderated the links between average levels of student-student and initial levels and developmental rates of creative potential.